Respuesta :
Answer:
a. xy+xy’ = x
b. (x+y)(x+y’) = x
c. (a+b+c’)(a’b’+c) = c (a + b) + a'b'c'
d. a’bc+abc’+abc+a’bc’ = b
e. (x+y)’(x’+y’) = x'y'
f. xy+x(wz+wz’) = x(y+w)
Explanation:
a) xy+xy’
= x ( y + y′ ) // taking x common
= x . 1 // y + y' = 1
= x
b) (x+y)(x+y’)
= xx + xy′ + yx + yy′ //multiplying x+y with x+y'
= x + xy′ + xy + 0 // xx = 1 yy' = 0
= x (1+ y′ + y) // taking x common
= x.1 // y+y' = 1
= x
c) (a+b+c’)(a’b’+c)
= aa'b' + ac + a'b'b + bc + a'b'c' + cc'
= 0 + ac + 0 + bc + a'b'c' + 0 // aa'= 0 bb'=0 cc'= 0
= ac + bc + a'b'c'
= c (a + b) + a'b'c'
d) a’bc + abc’ + abc + a’bc’
= b( a'c + ac' + ac + a'c') //taking b common
= b( a'c + a'c' + ac' + ac)
= b( a'(c+c') + a(c+c') // taking a common
= b(a'(1) + a(1)) //c+c' =1
= b(a'+a) //a+a'=1
= b(1)
= b
e) (x+y)'(x'+y')
= ( (x+y)'(x'+y') )
= ( (x+y) + (x'+y')' )'
= ( x + y + (x''y'') )'
= ( x + y + (xy) )'
= ( x +y + xy )'
= ( x ( 1 + y ) +y )'
= ( x + y )'
= x'y'
OR it can be done as :
e) (x+y)'(x'+y')
= x′y′ (x′+y′) //(x+y)' = x'y'
= x′y′ + x′y′ // (xy)' = x'+y'
= x′y′
f. xy+x(wz+wz’)
= xy + xw(z+z′) //taking w common
= xy + xw // z+z'=1
= x(y+w)
Boolean expressions are expressions that have values of 0 or 1.
(a) xy+xy’
Rewrite as:
[tex]\mathbf{xy+xy' = x(y + y')}[/tex]
Apply complementary law
[tex]\mathbf{xy+xy' = x.1}[/tex]
By identity law, we have:
[tex]\mathbf{xy+xy' = x}[/tex]
Hence, the simplified expression of xy + xy' is x
(b) (x+y)(x+y’)
Distribute the above expression
[tex]\mathbf{(x +y)(x + y') = xx + xy' + xy + yy'}[/tex]
Simplify
[tex]\mathbf{(x +y)(x + y') = x + xy' + xy + 0}[/tex]
[tex]\mathbf{(x +y)(x + y') = x + xy' + xy}[/tex]
In (a), we have: [tex]\mathbf{xy+xy' = x}[/tex]
So, the expression becomes
[tex]\mathbf{(x +y)(x + y') = x + x}[/tex]
This gives
[tex]\mathbf{(x +y)(x + y') = x }[/tex]
Hence, the simplified expression of (x + y)(x + y') is x
(c) (a+b+c’)(a’b’+c)
Distribute the above expression
[tex]\mathbf{(a + b + c)(a'b' +c) = aa'b' + ac + a'b'b + bc + a'b'c' + cc'}[/tex]
Apply complementary law
[tex]\mathbf{(a + b + c)(a'b' +c) = 0.b' + ac + a'.0 + bc + a'b'c' + 0}[/tex]
Simplify
[tex]\mathbf{(a + b + c)(a'b' +c) = ac + bc + a'b'c'}[/tex]
Distribute ac + bc
[tex]\mathbf{(a + b + c)(a'b' +c) = (a + b)c + a'b'c'}[/tex]
Hence, the simplified expression of (a + b + c)(a'b' +c) is (a + b)c + a'b'c'
(d) a'bc + abc' + abc + a'bc'
Distributive the above expression
[tex]\mathbf{a'bc + abc' + abc + a'bc' = (a'c + ac' + ac + a'c')b}[/tex]
Distribute
[tex]\mathbf{a'bc + abc' + abc + a'bc' = ((c+c')a' + (c+c')a)b}[/tex]
Apply complementary law
[tex]\mathbf{a'bc + abc' + abc + a'bc' = ((1)a' + (1)a)b}[/tex]
[tex]\mathbf{a'bc + abc' + abc + a'bc' = (a' + a)b}[/tex]
Apply complementary law
[tex]\mathbf{a'bc + abc' + abc + a'bc' = (1)b}[/tex]
Simplify
[tex]\mathbf{a'bc + abc' + abc + a'bc' = b}[/tex]
Hence, the simplified expression of a'bc + abc' + abc + a'bc' is b
(e) (x+y)'(x'+y')
Apply De Morgan's law
[tex]\mathbf{(x+y)'(x'+y')= x'y' (x'+y')}[/tex]
Apply De Morgan's law
[tex]\mathbf{(x+y)'(x'+y')= x'y' + x'y'}[/tex]
Simplify
[tex]\mathbf{(x+y)'(x'+y')= x'y'}[/tex]
Hence, the simplified expression of (x+y)'(x'+y') is x'y'
(f) xy+x(wz+wz')
Distribute
[tex]\mathbf{xy+x(wz+wz')= xy + x(z+z')w}[/tex]
Apply complementary law
[tex]\mathbf{xy+x(wz+wz')= xy + x(1)w}[/tex]
[tex]\mathbf{xy+x(wz+wz')= xy + xw}[/tex]
Distribute
[tex]\mathbf{xy+x(wz+wz')= (y + w)x}[/tex]
Hence, the simplified expression of xy + x(wz +wz') is (y + w)x
Read more about boolean expressions at:
https://brainly.com/question/19470209